The Study of the Strength of Eco-Bricks Containing Cockle Shell as Substitution Material - Azlan, Nur Ainna Amira; Mohd Yassin, Nurain Izzati (Recent Trends in Civil Engineering and Built Environment, 2026)
To significantly reduce environmental pollution and waste, it is necessary to find a substitute for cement. Cockle shells are found to have advantages as a substitute for cement in the construction of cement bricks because they are a renewable energy source and an environmentally friendly material. This study was conducted to examine the use of cockle shell powder (CSP) as a substitute for Ordinary Portland Cement (OPC) in the production of cement sand bricks (CSB). The percentage of CSP used as a cement substitute was 10%, 20%, and 30% of the cement composition, and it was cured for 7 and 28 days. The objective of this study is to optimize compressive strength and the optimal water absorption of cockle shell and to determine the initial absorption rate of bricks with different percentages of cockle shell waste as a substitute for cement. Compressive strength tests were conducted at 7 days and 28 days of age, while water absorption and the initial absorption rate were conducted at 28 days of curing. At the end of this study, CSP20 at the ages of 7 and 28 had the highest compressive strengths of 8.12 N/mm2 and 9.22 N/mm2. While CSP20 also has the highest value for water absorption, which is 14.49%. Then, the highest value for the initial absorption rate is CSP10 with 151.79 g/min/193.55 cm2. Overall, the CSB samples produced in this study comply with and exceed the established standards, making them suitable for use in the construction industry in Malaysia.